The Impact of Knowledge Sharing on the Services Provided by of Security and Safety Employees in Saudi Telecom Company - alghamdi, Yousef saeed (Arab Journal for Sciences and Research Publishing, 2020)
The study aimed to identify the impact of knowledge sharing on the services (customer service, preventive services) provided by security and safety employees in Saudi Telecom Company, to identify obstacles to knowledge sharing they face, and to identify the impact of knowledge sharing on them according to personal variables. The study used the descriptive-analytical method, and its population consisted of security and safety employees in Saudi Telecom Company, and it was applied to a random sample of (104) employees. The study used the questionnaire as a main tool for the study. The study came out with a number of results: 1) The reality of knowledge sharing with the various departments of Saudi Telecom Company came high. There is a positive impact of sharing knowledge with the safety and security employees of STC on customer service. 2) There is a high positive impact of knowledge sharing with security and safety employees in Saudi Telecom Company on the preventive services provided by them. 3) The degrees of assessment of the respondents about the obstacles to knowledge sharing with the employees of security and safety in Saudi Telecom Company came in a neutral degree, and the highest expressions that expressed obstacles in terms of average, which respondents affirmed the existence of (the belief of some employees in the Saudi Telecom Company that their knowledge is the source of their strength they can from During which to achieve distinction from others, the absence of a culture of knowledge sharing among employees in STC. " 4) There is a positive impact of knowledge sharing on the services provided by the employees of security and safety in STC. 5) There are no statistically significant differences between the responses of the sample members regarding the effect of knowledge sharing on the services provided by the employees of security and safety in Saudi Telecom Company that are attributed to variables (years of experience, educational qualification). In light of the results, the study recommended the following: 1) The need to work on designing knowledge portals to facilitate the task of security employees within the telecommunications company to share knowledge. 2) The need to develop a clear and explicit strategy to enhance knowledge sharing among employees in the company.
Keywords: Knowledge Sharing; Services Provided; Security and Safety Personnel; Saudi Telecom Company